Handbook of Positive Psychology, Religion, and Spirituality 2022
DOI: 10.1007/978-3-031-10274-5_10
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychology and Christianity

Abstract: Both theoretical reflection and empirical research have purported a mutual exchange of benefits for the collaboration between positive psychology (PP) and Christianity. However, the varied belief systems and worldviews held among adherents of distinct Christian traditions may interfere with practical collaborative efforts between PP and Christianity. In this chapter, we explore important considerations for effective collaboration between PP and Christianity. Namely, we argue that Christianity can provide a fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Theorists and researchers have posited that collaborative efforts between positive psychology, including the study of grace, and Christianity can be mutually beneficial (Charry & Kosits, 2017). On one hand, R/S traditions can provide a framework for what individuals should value (e.g., grace), whereas positive psychology can provide the tools and methodology for how to improve in these areas (Hodge et al, 2023). Results from this article can aid in continuing this collaborative effort, and perhaps also stand as a reference point for the study of grace to be qualitatively and quantitatively explored in other R/S traditions throughout the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theorists and researchers have posited that collaborative efforts between positive psychology, including the study of grace, and Christianity can be mutually beneficial (Charry & Kosits, 2017). On one hand, R/S traditions can provide a framework for what individuals should value (e.g., grace), whereas positive psychology can provide the tools and methodology for how to improve in these areas (Hodge et al, 2023). Results from this article can aid in continuing this collaborative effort, and perhaps also stand as a reference point for the study of grace to be qualitatively and quantitatively explored in other R/S traditions throughout the world.…”
Section: Discussionmentioning
confidence: 99%
“…However, as demonstrated in this article, experiences of, and beliefs about, divine grace can vary significantly, even within similar denominations. The global landscape of R/S is changing rapidly (Pew Research Center, 2017), and perhaps perspectives of divine grace will shift with these changes (Hodge et al, 2023). This study reported on the results of experiences of, and beliefs about, divine grace in a predominately White sample of Mainline Protestants who live in the Southwestern United States.…”
Section: Significance Of This Articlementioning
confidence: 99%